2019
DOI: 10.1016/j.whi.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Use of Race in the Vaginal Birth after Cesarean Section Calculator

Abstract: (D.A. Vyas). 1 Predicted probability of successful VBAC ¼ exp (w)/[1 þ exp(w)] where w ¼ 3.766-0.039(age)-0.060(prepregnancy body mass index)-0.671(African American race)-0.680(Hispanic race) þ 0.888(any prior vaginal delivery) þ1. 003(vaginal delivery after prior cesarean)-0.632(recurring indication for cesarean).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 21 publications
0
60
0
1
Order By: Relevance
“…The use of racial classification in defining or calculating seemingly objective clinical data has faced criticism. Studies, such as a recent article by Vyas et al, detail the use of clinical calculators that integrate race, such as pulmonary function tests and a vaginal birth after cesarean section calculator, and their potential impact on health inequities [30][31][32] ; the authors warn against the use of race as a proxy for genetic difference. Co-authors (NE and PR) highlighted that eGFR equations enable assessments of CKD prevalence over time in populations, but the inclusion of a race term creates problems at the bedside for patients who identify as mixed race or reject racial categorization.…”
Section: Discussionmentioning
confidence: 99%
“…The use of racial classification in defining or calculating seemingly objective clinical data has faced criticism. Studies, such as a recent article by Vyas et al, detail the use of clinical calculators that integrate race, such as pulmonary function tests and a vaginal birth after cesarean section calculator, and their potential impact on health inequities [30][31][32] ; the authors warn against the use of race as a proxy for genetic difference. Co-authors (NE and PR) highlighted that eGFR equations enable assessments of CKD prevalence over time in populations, but the inclusion of a race term creates problems at the bedside for patients who identify as mixed race or reject racial categorization.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study concerned a low risk group, and it seems unlikely that women from all non-western regions should have undiagnosed and unrecorded medical risks affecting TOLAC failure to the extent observed. A more plausible explanation might be cultural and language barriers affecting use of antenatal care, the patient-doctor rapport, and clinical decisions [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…maternal attitudes, lifestyle factors, and practitioners' attitudes. To explore this further and counter it on a policy level appears more appropriate than accepting the observed determinants as non-modifiable elements in clinical decision-making [35,38].…”
Section: Discussionmentioning
confidence: 99%
“…McMurray [50] Decolonizing entry to practice: Reconceptualizing methods to facilitate diversity in nursing programs 1.Implement a framework for academic application review processes that addresses structural barriers that affect access, including those unique to students from diverse backgrounds 2.Evaluate and build pipeline programs to support expansion of diversity prior to point-of-entry to practice nursing 3.Work to retain diverse faculty by having intentional steps to improve work culture and environment surrounding their educational practice Shappell and Schnapp [48] The F word: how "fit" threatens the validity of resident recruitment 1.Establish a clear brand identity for your educational program to guide discussion regarding culture 2.Take a holistic approach toward fit, diversity, and program culture 3.Learn biases 4.Follow up on gestalt impressions Yang [17] What should be taught and what is taught: Integrating gender into medical and health professions education for medical and nursing students 1.Allow educators to develop a gender education learning map for students by determining the core gender knowledge needed and identifying the gender-related concepts to be integrated 2.Universities should pay attention to professional development of educators in gender education Educating workforce for diversity Nong et al [52] Patient-reported experiences of discrimination in the U.S. healthcare system 1.Organizations should explore reports of discrimination by engaging patient stories most likely to be present in the healthcare setting -use this data to inform organizational policy Vyas et al [53] Challenging the use of race in the vaginal birth after cesarean section calculator 1.Remove race-based consideration to calculation of risk for vaginal delivery after cesarean section and educate future clinicians to base recommendation on patient specific presentation crucial step in challenging stereotypes involves empowering faculty with the freedom and support to counter/correct biased or stereotypical language and attitudes from the classroom to the practice environment. This act will help future health professional students develop more complex portraits of patients/caregivers from backgrounds that differ, because it will highlight respectful allyship.…”
Section: Recruiting Diverse Students and Facultymentioning
confidence: 99%